Principles for fostering the transdisciplinary development of assistive technologies. (4th July 2017) - Boger, Jennifer; Jackson, Piper; Mulvenna, Maurice; Sixsmith, Judith; Sixsmith, Andrew; Mihailidis, Alex; Kontos, Pia; Miller Polgar, Janice; Grigorovich, Alisa; Martin, Suzanne
Abstract: Developing useful and usable assistive technologies often presents complex (or "wicked") challenges that require input from multiple disciplines and sectors. Transdisciplinary collaboration can enable holistic understanding of challenges that may lead to innovative, impactful and transformative solutions. This paper presents generalised principles that are intended to foster transdisciplinary assistive technology development. The paper introduces the area of assistive technology design before discussing general aspects of transdisciplinary collaboration followed by an overview of relevant concepts, including approaches, methodologies and frameworks for conducting and evaluating transdisciplinary working and assistive technology design. The principles for transdisciplinary development of assistive technologies are presented and applied post hoc to the COACH project, an ambient-assisted living technology for guiding completion of activities of daily living by older adults with dementia as an illustrative example. Future work includes the refinement and validation of these principles through their application to real-world transdisciplinary assistive technology projects. Implications for rehabilitation: Transdisciplinarity encourages a focus on real world 'wicked' problems. A transdisciplinary approach involves transcending disciplinary boundaries and collaborating with interprofessional and community partners (including the technology's intended users) on a shared problem. Transdisciplinarity fosters new ways of thinking about and doing research, development, and implementation, expanding the scope, applicability, and commercial viability of assistive technologies.